Pengaruh Pemahaman Peraturan Perpajakan, Kemudahan Pelaporan Perpajakan, dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Pada Pengusaha Online di Aplikasi Shopee - Putri Yuniar Putri; Siti Isnaniati; Rike Selviasari (Jurnal Proaksi, 2025)
Main Purpose - This study aims to examine the effect of understanding tax regulations, ease of tax reporting, and tax socialization, on taxpayer compliance in online entrepreneurs in the Shopee Application.Method - The population used in this study were all questionnaires distributed via chat on the Shopee platform. The data used was collected based on the voluntary sampling method and a sample of 75 respondents was obtained. The method used in this research is a quantitative method using SPSS. Main Findings - The results of this study reveal that the variables of understanding tax regulations and tax reporting have no effect on taxpayer compliance in online entrepreneurs in the shopee application and the ease of tax socialization affects taxpayer compliance in online entrepreneurs in the shopee application. Theory and Practical Implications - The results of this study have theoretical implications that strengthen the relevance of attribution theory and Theory of Planned Behavior (TPB) in the context of tax compliance of e-commerce business actors. In attribution theory, individual behavior is influenced by perceptions of internal and external factors. The finding that understanding and ease of tax reporting have no significant effect on taxpayer compliance, but tax socialization has a positive effect, shows that external perceptions built through education and information from tax authorities are able to change taxpayer attitudes. This is also in line with TPB, which states that the intention to behave (in this case, to comply with paying taxes) is influenced by attitudes towards behavior, subjective norms, and perceived behavioral control. Effective tax socialization can form positive attitudes and social norms that encourage compliance, especially for e-commerce players who are generally young and do not have a strong understanding of taxes.Novelty - The novelty in this research is the object of online entrepreneurs in the Shopee application.